Improved Learning Outcomes of My Job as a Religious Community through Scientific Approach Aided by Power Points in Class II elementary schools - Andriyani, Fauziah Ratna (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The background of this research is the low learning outcomes of grade II SD 2 Jepang Pakis on the subject of My Task as a Religious Person. The aim of this research is to describe the application of the powerpoint assisted scientific approach to improve the learning outcomes of the material My Task As a Religious in grade II SD 2 Jepang Pakis. This research is a Classroom Action Research which lasts for two cycles. The subjects of this reseach were second grade students of SD 2 Jepang Pakis, Jati District, Kudus Regency. Data collection techniques used are through observation, tests, and documentation. In the first cycle, 65% of students reached the KKM and the remaining 35% had not reached the KKM with a mean score of 78. While in the second cycle there were 87% of students who reached the KKM and the remaining 13% had not reached the KKM with a mean score of 83. Based on these results , it can be concluded that the use of a scientific approach combined with PowerPoint media can improve the learning outcomes of grade II SD 2 Jepang Pakis in the academic year 2020/2021 for my assignment as a religious community.